Collisions with another person while skiing and snowboarding: A 13-year national registry analysis. Issue 7 (July 2022) - Wallner, Bernd; Rugg, Christopher; Paal, Peter; Ströhle, Mathias
Highlights: Collisions predominantly occurred on slopes during a downhill run; collisions of two snowboarders more often also occurred in terrain parks. In collisions head injuries were the most frequent location, contusions, strains or sprains and fractures the most frequent type of injury. In skier versus snowboarder collisions the skier had a nearly eight-fold higher risk of being injured more severely. Skiers wearing a helmet had an increased risk for being the more severely injured when colliding with another skier. Risk factors for being the more severely injured in collisions were female gender and standing or sitting in the snow prior to the collision. Abstract: Introduction: Interindividual collisions while skiing or snowboarding occur regularly, they can be associated with severe injuries. Objective: To elucidate causes of accidents, injury patterns and potential risk factors for injury severity in interindividual collisions of skiers and snowboarders. Material and Methods: Retrospective analysis of the Austrian Registry for Mountain Accidents within a 13-year timeframe (2005–2018) with regard to on- or off-piste collisions of skiers and snowboarders. Results: A total of 30, 503 collisions, involving 52, 430 (85.9%) skiers and 8, 576 (14.1%) snowboarders were analysed. Denominators are lacking, since total numbers of skiers and snowboarders were not available. Compared to skiers, snowboarders were younger (23 vs. 42 years; p <0.001), predominantly male (77.4% vs. 61.0%; p <0.001) and less often severely injured (46.8% vs. 26.2%; p <0.001). Most accidents occurred on slopes (>95%). Collisions involving two snowboarders occurred proportionally more often in terrain parks (4.1% of 1, 664 injured snowboarders; p <0.001) and while one victim was standing or sitting (9.7%; p <0.001). Contusions/strains/sprains were most prevalent (>23%), as were head injuries (>12%). In skiers, chest, shoulder, hip, thigh and knee injuries occurred more often, leading to fractures, dislocations, concussions and internal injuries more frequently. In snowboarders, spine/back, elbow, forearm, wrist and lower leg injuries were more prevalent. Female gender and standing or sitting prior to the accident was a risk factor for being more severely injured in collisions involving i) two skiers (OR: 4.02 (3.79–4.26) and 3.91 (3.26–4.68)), ii) a skier and a snowboarder (OR: 4.50 (3.95–5.14) and 11.49 (8.04–16.41)) or iii) two snowboarders (OR: 2.85 (2.12–3.84) and 12.47 (6.17–25.20)). Wearing a helmet increased the risk when two skiers collided (OR: 1.10 (1.03–1.17)). In skier vs. snowboarder collisions, the skier had a higher risk of being injured more severely (OR: 7.93 (6.98–9.01)). Conclusions: In interindividual collisions of skiers and snowboarders, injury patterns and preceding causes differ substantially. Skiers are more likely to be severely injured. Awareness of an increased risk of injury should be raised particularly while standing or sitting on the slope.